DETERMINATION OF ALPHAFETOPROTEIN (AFP) LEVEL IN THE HEPATITIS B CARRIERS WITH DIFFERENT MALIGNANT DISEASES BY RADIOIMMUNOASSAY TECHNIQUE (A PILOT STUDY) - WIWANITKIT, Viroj; SUWANSAKSRI, Jamsai (The ASEAN Journal of Radiology, 2023)
Alpha-fetoprotein (AFP) , is a commonly used tumor marker in the present day. In the Individuals with chronic hepatitis B are at increased risk for the development of hepatocellular carcinoma. Although precise recommendations do not exist, it is reasonable for such individuals to undergo periodic screening for cancer. Screening procedures include measurement of serum alpha-fetoprotein (a tumor marker that is elevated in about 85% of individuals with hepatocellular carcinoma) and ultrasound examination. Here we reported the study of serum AFP levels determined by radioimmunoassay technique in the hepatitis B carriers with various malignant diseases. This study was designed as a descriptive pilot study. The serum AFP levels from 7 hepatitis B carriers with different malignant diseases, 3 with hepatoma (Child Class C) and 4 with nonhepatoma, were used in this study. All were the confirmed cases of hepatitis B infection without concomitant of other hepatitis. The radioimmunoassay kit used in this study was ELISA-AFP (CIS Bio International). It was noted that a great variations of the AFP levels among the hepatoma subjects were observed although we used the patient in the same Child classification. However, comparing to the other 10 selected non hepatitis B carriers with hepatoma (Child Class C), wide range of serum AFP was also observed. Furthermore, some overlapping of the AFP levels between hepatoma and non-hepatoma group was observed. We also studied the serum AFP levels among the other 10 hepatitis B silent carriers without evidence of liver structural pathology (from ultrasonography study) and revealed that the average AFP level was comparable to the malignant group. Furthermore, using the ANOVA analysis, there was no significant difference among the four groups of subjects (P = 0.176). Hence, the serum AFP level may not be a good screening tool for hepatoma in the hepatitis B carriers.